High-velocity nasal insufflation in dogs with left-sided congestive heart failure unresponsive to traditional oxygen therapy: a retrospective case series - Bailey Lane; Rebecca A. Walton; Rebecca A. Walton; April E. Blong; Meredith ‘t Hoen; Melissa A. Tropf; Jessica L. Ward; Allison K. Masters (Frontiers in Veterinary Science)
ObjectiveTo describe high–velocity nasal insufflation (HVNI) for managing dogs with left–sided congestive heart failure (L–CHF) failing traditional oxygen therapy (TOT). To secondarily evaluate complications based on retrospective evaluation of the record of HVNI and survival to discharge.DesignRetrospective case series from a university teaching hospital between August 2019 and October 2021.AnimalsTwelve dogs diagnosed with L-CHF and managed with HVNI.Measurements and main resultsMedical records were retrospectively reviewed for signalment, point-of-care diagnostics, and HVNI information. Nine dogs were diagnosed with myxomatous mitral valve disease, and three dogs were diagnosed with dilated cardiomyopathy. All dogs in this study required HVNI after failing TOT. Dogs were treated with HVNI for a median of 14 h (range 2–22 h). HVNI was successfully discontinued in 10 dogs (83%), all of which survived to discharge. Two dogs on HVNI were humanely euthanized, both of which were diagnosed with Stage D refractory CHF. No major complications of HVNI were noted in any dogs.ConclusionHVNI is a potential method of escalating oxygen support for dogs in L-CHF who fail TOT. In this case series, all dogs in which HVNI was successfully discontinued survived to discharge.